Congenital double duodenal diaphragms in an infant - Shilpa Sharma; Sukhjeet Singh; Amita Sen (Wolters Kluwer Medknow Publications, 2013)
Duodenal stenosis usually occurs in isolation and has a variable presentation in infancy due to partial obstruction.An unusual case of congenital double duodenal diaphragms in an infant presenting as failure to thrive has been described and pertinent literature has been reviewed herein. Excision of webs with double Heineke-Mikulicz closure was performed.